2010
DOI: 10.1177/0022022109359692
|View full text |Cite
|
Sign up to set email alerts
|

Indecisiveness and Culture: Incidence, Values, and Thoroughness

Abstract: Three studies examined cultural variations in indecisiveness among Chinese, Japanese, and Americans. In Study 1, validated self-report, comprehensive measures of indecisiveness indicated large cultural differences, with Japanese participants exhibiting substantially more indecisiveness than Chinese or Americans. Study 2 provided evidence that such cultural variations correspond to variations in people’s positive versus negative values for decisive behaviors, suggesting that such values are plausibly an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 24 publications
(28 reference statements)
1
31
1
Order By: Relevance
“…Many between-and withinregion comparisons have been made, and some results are inconsistent. Regarding East/West contrasts, researchers found most East Asian groups -including participants from Japan, Hong Kong, and Taiwan -to be more indecisive than Westerners of European heritage (Li, Masuda, & Russell, 2014;Mann et al, 1998;Yates et al, 2010). Results for mainland Chinese comparisons have been mixed, although leaning toward the side of higher Chinese decisiveness; Tse, Lee, Vertinsky, and Wehrung (1988) found mainland Chinese to be more decisive than Hong Kongers and Canadians, but Patalano and Wengrovitz (2006) found no difference between mainland Chinese and Americans.…”
Section: Investment: ''What Will It Cost To Make This Decision?"mentioning
confidence: 99%
See 1 more Smart Citation
“…Many between-and withinregion comparisons have been made, and some results are inconsistent. Regarding East/West contrasts, researchers found most East Asian groups -including participants from Japan, Hong Kong, and Taiwan -to be more indecisive than Westerners of European heritage (Li, Masuda, & Russell, 2014;Mann et al, 1998;Yates et al, 2010). Results for mainland Chinese comparisons have been mixed, although leaning toward the side of higher Chinese decisiveness; Tse, Lee, Vertinsky, and Wehrung (1988) found mainland Chinese to be more decisive than Hong Kongers and Canadians, but Patalano and Wengrovitz (2006) found no difference between mainland Chinese and Americans.…”
Section: Investment: ''What Will It Cost To Make This Decision?"mentioning
confidence: 99%
“…High need for cognition, by definition, would also promote more cognitive investment in the decision-making process. Yates et al (2010) proposed that relevant norms common in China and Japan might differ despite their shared collectivism; Japanese might be especially indecisive because they value indecisiveness, perhaps under a more flattering label such as ''thoroughness." The Japanese participants of Yates et al (2010) reported being more indecisive than Chinese and Americans, and they were more likely than Chinese and Americans to admire indecisive people, too.…”
Section: Investment: ''What Will It Cost To Make This Decision?"mentioning
confidence: 99%
“…Part of this may be cultural difference in decision making and related to this, values of various cultures. In one study of Chinese, Japanese, and American populations, it was found that Japanese individuals experienced far more indecision than the Chinese and American participants (Yates et al, 2010). The authors attributed this to Japanese culture's attention to thoroughness, more so than Chinese and American cultures, and suggest that this is perhaps a reason that Japanese individuals may experience more DCDM (Yates et al, 2010).…”
Section: Saltermentioning
confidence: 99%
“…In one study of Chinese, Japanese, and American populations, it was found that Japanese individuals experienced far more indecision than the Chinese and American participants (Yates et al, 2010). The authors attributed this to Japanese culture's attention to thoroughness, more so than Chinese and American cultures, and suggest that this is perhaps a reason that Japanese individuals may experience more DCDM (Yates et al, 2010). Another study examined the levels of indecision between American college students and Peruvian college students and found that American students experienced more indecision than their Peruvian counterparts (Arce, 1995).…”
Section: Saltermentioning
confidence: 99%
“…A primary question for the choice overload hypothesis is which of the potential moderating factors lead to detrimental outcomes in a decision‐making context as vital as treatment choice. Prior research on cross‐cultural differences in cognition and decision making suggests these broader socio‐cultural factors may be central to determining when overload effects will manifest (e.g., Greifeneder et al, ; Iyengar & Lepper, ; Miller, Das, & Chakravarthy, ; Yates et al, ). The current research explored this novel question and extends prior work on choice over placebo treatments, which, until now, has focused on individuals in a Western cultural context.…”
Section: Choice and Choice Complexitymentioning
confidence: 99%